IMPLEMENTATION OF CROSS-CULTURAL COUNSELING IN SCHOOLS - Azzahwa, Meyrina; Anastasya, Lia (Program Studi Bimbingan dan Konseling FKIP UNJA, 2023)
Indonesia has a diverse culture from Sabang to Merauke which consists of thousands of unique, interesting islands and tribes and each region has different tribes. Cross-cultural counseling is a counseling service process that involves counselors and counselees from different cultural, ethnic and characteristic backgrounds, so it is very sensitive to cultural bias in counseling. Students really need the implementation of cross-cultural counseling at school, therefore the ability to carry out cross-cultural counseling is highly expected from counselors or guidance and counseling teachers at school. Counseling is a process provided by counselors to individuals to overcome problems or obstacles. Culture is a compound of cultivation, which means the power of the mind. Cross-cultural counseling involves counselors and counselees from different cultural backgrounds, and the counseling process is very sensitive to the counselor's cultural bias, so that counseling becomes ineffective, teachers must be culturally sensitive and free from cultural bias, understand and appreciate cultural diversity, and have sensitive skills culture.